One Health Evaluation: A Case Study at the University of Bologna - Aragrande, Maurizio; Canali, Massimo; Roccaro, Mariana; Ferraro, Elisabetta; Bonoli, Alessandra; Savini, Federica; Piva, Silvia; Gallina, Laura; Peli, Angelo; Sambri, Vittorio; Scagliarini, Alessandra (Frontiers in Public Health, 2021)
The level of One Health (OH), or “One Health-ness,” of health interventions has been defined as the capacity to operate according to six dimensions concerning OH operations and OH infrastructures, respectively (thinking, planning, and working; and information sharing, reciprocal learning, and systemic organization). Although health initiatives and research increasingly claim their orientation toward OH, such a capacity is rarely assessed. The objective of this study is to evaluate the One Health-ness of the academic team of the University of Bologna (UNIBO Team) working in the “ELEPHANT” project (Empowering universities' Learning and rEsearch caPacities in the one Health Approach for the maNagement of animals at the wildlife, livestock and human interface in SouTh Africa). This project involves universities, six from South Africa and two from Europe, and aims at embedding OH in research and learning to enable the control of diseases at the human, animal, and environmental interface, and to emphasize the interests of local African communities with wildlife conservation. The methodology adopts the NEOH method, developed in 2018 by the EU-COST Action, “Network for the Evaluation of One Health.” The approach is based on questionnaires delivered to participants, which focus on the six OH dimensions, and then translate answers into quantitative metrics through the OH Index (OHI) and the OH Ratio (OHR). The following two evaluation levels are foreseen: the whole project and the single partner institutions. The evaluations are carried on in parallel, with preliminary, mid-term, and final assessments, to monitor the efficacy of the project actions. The preliminary evaluation of the UNIBO Team resulted in the OHI of 0.23 and the OHR of 1.69 which indicate a low degree of OH-ness and an imbalance between OH operation and OH infrastructure. The UNIBO case study will be the baseline for the evaluation of the other partner institutions involved in the ELEPHANT project. This type of evaluation can support the implementation of OH practices inside a project and underpin the strategies that allow to achieving more effective results. Any improvement in the OH-ness of each single academic team can be also considered as a result of the ELEPHANT project, thus showing its multiplier effect in the context.